A framework for flow time measured by Doppler ultrasound - Kenny, Jon‑Emile S. (The Ultrasound Journal, 2025)
The duration of mechanical systole—also termed the flow time (FT) or left ventricular ejection time (LVET)—is measured by Doppler ultrasound and increasingly used as a stroke volume (SV) surrogate to guide patient care. Nevertheless, confusion exists as to the determinants of FT and a critical evaluation of this measure is needed. Using Doppler ultrasound of the left ventricular outflow tract velocity time integral (LVOT VTI) as well as strain and strain rate echocardiography as grounding principles, this brief commentary offers a model for the independent influences of FT. This framework establishes that systolic duration is directly proportional to the distance traversed by a single cardiac myocyte and indirectly proportional to its shortening velocity. Grossly, this translates to a direct relationship between FT and the LVOT VTI (i.e., SV) and an indirect relationship with mean ejection velocity. Thus, changes in the systolic time can infer SV change, so long as other cardiac parameters are considered.